2010
DOI: 10.3109/09286580903450346
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Visual Impairment in the Adult Japanese Population by Cause and Severity and Future Projections

Abstract: This comprehensive study presents the prevalence of total visual impairment in the adult Japanese population. The projected increases in the prevalence of visual impairment over time reflect the demographic changes of a declining and aging Japanese population. These projections highlight that the burden of disease due to visual impairment and imposed on society is likely to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 27 publications
2
119
1
2
Order By: Relevance
“…This was based on the marked differences in the epidemiology of myopia and pathological myopia between East-Asians (e.g., Chinese, Japanese) and Caucasians. The prevalence of myopic CNV is higher in East-Asian patients than in Caucasians [1,2,3,6,12]. Variations in the genetic predisposition to, and risk factors for, myopia may therefore influence possible observed differences in the natural history of myopic CNV in East-Asian and Caucasian patients [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was based on the marked differences in the epidemiology of myopia and pathological myopia between East-Asians (e.g., Chinese, Japanese) and Caucasians. The prevalence of myopic CNV is higher in East-Asian patients than in Caucasians [1,2,3,6,12]. Variations in the genetic predisposition to, and risk factors for, myopia may therefore influence possible observed differences in the natural history of myopic CNV in East-Asian and Caucasian patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is a common condition that varies in geographic prevalence [1,2,3,4]. Studies have shown that Asian countries generally have a higher prevalence of myopia, up to 70-90%, compared with 25-50% in Western Europe [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Polypoidal choroidal vasculopathy (PCV) is a disease entity that shares some clinical features similar to wet-AMD. [6][7][8][9] Yet, characteristic differences exist between the two entities in terms of pathogenesis, clinical features, and natural history.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It is characterized by excessive axial elongation of the eye, scleral thinning, posterior staphyloma, chorioretinal atrophy, and choroidal neovascularization. 6 The prevalence of MMD in East Asia is estimated to be 1.7% to 3.1%, 7,8 but because MMD also affects young and middle-aged working adults, 9,10 it carries a significant socioeconomic burden.…”
mentioning
confidence: 99%